Mixed nerve conduction study in the diagnosis of ulnar neuropathy at the elbow - Selahattin Ayas; Elif Simin Issi (Neurological Sciences and Neurophysiology, 2023)
Purpose: This study aims to investigate the ulnar-median mixed nerve latency difference (U-MLD) recorded from the medial aspect of the arm both in patients with ulnar neuropathy at the elbow (UNE) and in healthy individuals and thus to assist in the diagnosis of UNE. Materials and Methods: Twenty-nine patients meeting electrophysiological criteria defined by the American Association of Neuromuscular and Electrodiagnostic Medicine for diagnosis of UNE, and 50 healthy individuals were included in the study retrospectively. All participants' data were evaluated, such as median/ulnar motor and sensory response, U-MLD and the percentage of ulnar mixed nerve response amplitude difference between sides. Results: The U-MLD was significantly higher in patients with UNE than in the control group (1.78 ± 0.64 ms vs. 0.6 ± 0.22 ms, P = 0.000). The percentage of the ulnar mixed nerve response amplitude loss was significantly higher in the patient group compared to the control group (43.9% ± 30.3% vs. 21.4% ± 12.2%, P = 0.018). The U-MLD was significantly higher in the patients with amplitude loss ≥50%, and the ulnar mixed nerve response amplitude loss was ≥50% in all five patients with the ulnar sensory nerve action potential pathology. Conclusions: U-MLD is higher in patients with UNE; it can provide additional data in mild cases regarding the diagnosis of UNE, especially. Furthermore, the criterion that the ulnar mixed nerve response amplitude difference between the sides ≥50% suggests that it can be used to evaluate the severity of UNE.